Analisis Perilaku Agresi Pengguna Aplikasi Kencan Online pada Gen Z - Sischa Wahyu Wardani; Anisa Arwah Lia; Ishma Annisa; Abdullah Azzam Al Afghani (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Technological developments have given birth to various cutting-edge applications, including online chatting applications, online motorcycle taxis, shopping, and online dating applications. Social media and online applications can be easily accessed by various groups of society. Aggressive behavior is behavior that aims to hurt or harm other people who do not want it. This research uses a qualitative phenomenological method. A phenomenological approach was used to understand generation Z's subjective experience of open relationships through the use of online dating applications. The formulation of the problem in this research is, what are the characteristics of aggressive behavior that appear among online dating application users among Generation Z and what factors influence this. This research aims to understand the dynamics of aggressive behavior that occurs among online dating application users in Generation Z. In addition, this research aims to explore and understand various types of aggression, including physical, verbal and relational.